2018
DOI: 10.1111/jvim.15050
|View full text |Cite|
|
Sign up to set email alerts
|

Variability of Symmetric Dimethylarginine in Apparently Healthy Dogs

Abstract: BackgroundSymmetric dimethylarginine (SDMA) is a screening tool for early kidney dysfunction and monitoring treatment in cases of chronic kidney disease (CKD). There are no current studies describing the suitability of this test for use with published population‐based reference intervals.Hypothesis/ObjectivesTo determine the components of biological variability, the index of individuality (IOI), the critical difference between sequential measurements (C D) and the number of measurements required to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
4
37
0
2
Order By: Relevance
“…For dogs with no suspicion of renal disease, repeating single SDMA measurement between 15 and 19 μ g/dL is recommended [ 30 ], but this was not possible due to the retrospective nature of our study. Some authors also have suggested that young dogs and Greyhounds might have a URL higher than 14 μ g/dL [ 18 , 36 ], and in a recent study [ 42 ], the mean SDMA concentration of 20 apparently healthy dogs (12.7 μ g/dL) was situated in the top quarter of the population-based reference interval established by IDEXX Laboratories. Therefore, in order to reduce the number of dogs with doubtful SDMA classification (range 15–19 μ g/dL), we decided to use SDMA >19 μ g/dL as a clinical decision cut-off value for both control dogs and dogs with leishmaniosis to increase the specificity of the test in spite of a decrease in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…For dogs with no suspicion of renal disease, repeating single SDMA measurement between 15 and 19 μ g/dL is recommended [ 30 ], but this was not possible due to the retrospective nature of our study. Some authors also have suggested that young dogs and Greyhounds might have a URL higher than 14 μ g/dL [ 18 , 36 ], and in a recent study [ 42 ], the mean SDMA concentration of 20 apparently healthy dogs (12.7 μ g/dL) was situated in the top quarter of the population-based reference interval established by IDEXX Laboratories. Therefore, in order to reduce the number of dogs with doubtful SDMA classification (range 15–19 μ g/dL), we decided to use SDMA >19 μ g/dL as a clinical decision cut-off value for both control dogs and dogs with leishmaniosis to increase the specificity of the test in spite of a decrease in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, 1 we made a mathematical error in the calculation of C D and RCV, and hence, we have recalculated these values for the study cohort means for symmetric dimethylarginine (SDMA) and creatinine and found them to be 5.98 μg/dL (RCV of 47%) and 22.8 μmol/L (RCV 23.7%), respectively. It is of note that these recalculated C D and RCV values indicate greater biological and analytical variability for these variables.…”
mentioning
confidence: 99%
“…Not being fasted and higher muscle mass are possible reasons for increased creatinine as well, however, this would also apply for the control dogs. Determination of symmetric dimethylarginin (SDMA) would have helped to exclude this influence but was not available when the study was performed [20]. Therefore, it is possible that some of the dogs would not have been classified as dogs with renal disease if repeated measurements of creatinine and USG or measurement of glomerular filtration rate (GFR) were performed to confirm the presence of renal disease.…”
Section: Discussionmentioning
confidence: 99%